The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.5006/1.3290339
|View full text |Cite|
|
Sign up to set email alerts
|

Mass-Transport-Limited Oxygen Reduction Reaction on AA2024-T3 and Selected Intermetallic Compounds in Chromate-Containing Solutions

Abstract: Oxygen reduction reaction (ORR) kinetics were investigated on synthesized Al-Cu, Al-Cu-Mg, and Al-Cu-Fe-Mn intermetallic phases and compared toAA2024-T3 (UNS A92024), as well as high-purity Al, Cu, and Au. These tests were conducted in 0.1 M sodium sulfate (Na 2 SO 4 ) with and without either 0.005 M sodium chloride (NaCl, pH 6), 0.01 M sodium chromate (Na 2 CrO 4 , pH 8), or 0.0062 M Na 2 CrO 4 + 0.0038 M chromic acid (H 2 CrO 4 , pH 6) additions using stationary and rotating disk electrodes. Mass-transport-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 36 publications
4
118
0
1
Order By: Relevance
“…Since E P1 is related to dissolution of Al 2 CuMg, the absence of such transient event seems to indicate that the clear metavanadate solutions suppressed the dissolution of S-phases until the potential reached E P2 . As explained by Ilevbare and Scully [55,56], reducing the dissolution of Al 2 CuMg particles reduces the formation of Cu rich cathodic sites. In most of our experiments, however, AA2024-T3 samples were exposed to 0.5 M NaCl for at least 15 min before injecting the inhibitors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Since E P1 is related to dissolution of Al 2 CuMg, the absence of such transient event seems to indicate that the clear metavanadate solutions suppressed the dissolution of S-phases until the potential reached E P2 . As explained by Ilevbare and Scully [55,56], reducing the dissolution of Al 2 CuMg particles reduces the formation of Cu rich cathodic sites. In most of our experiments, however, AA2024-T3 samples were exposed to 0.5 M NaCl for at least 15 min before injecting the inhibitors.…”
Section: Discussionmentioning
confidence: 91%
“…The E P was the same with or without the inhibitor, showing that the presence of clear metavanadate did not affect the anodic reaction (in this case localized Al dissolution). Cathodic polarization curves of Cu in aerated 0.5 MNaCl electrolytes with no inhibitor added are characterized by a large limiting current (i L ) of about -320 µA/cm 2 due to the strong stirring and air bubbling of the electrolyte [55][56][57]. Evolution of hydrogen gas was observed at potentials below -1.2 V SCE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the presence of chromate ions inhibits open-circuit potential corrosion and Al 2 CuMg dissolution (anodic inhibition), reduces pitting (anodic inhibition), and inhibits cathodic ORR (cathodic inhibition). [23][24] Therefore, one benefi cial role of chromate during scribe-creep can be interpreted through its role in minimizing Cu replating. The other is the well-known effect of enhanced adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…As was stated above, the IMC for this alloy are primarily of the Al-Cu, Al-Cu-Mg, and Al-Cu-Mn-Fe compositions. [2][3]5,7,[10][11][12][13][14][15][21][22]24 Using scanning electron microscopy (SEM) and image analysis, the surface area ratio for coarse constituent-type IMC was 2.18%, with an average IMC diameter of 2.43 µm (Figure 1) after stereological correction using the Saltyov (area) method. [52][53] The L 2 statistical point pattern spatial analysis [54][55] performed on the IMC on the long transverse (LT) or rolling surface showed that the IMC are sometimes clustered and sometimes random, as can…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation